Purveyors of change : school leaders of color share narratives of student, school, and community success - Alston, Judy A.; Scott, Lawrence; Alexander, Sheree N. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Effective leadership is the necessary ingredient in achieving educational improvement in schools; everything rises and falls on leadership. For School Leaders of Color, this leadership imperative is more difficult than it is for their White counterparts. Concomitantly with this leadership necessity are the social and academic disparities of racism, student poverty, lack of resources, just to name a few. Yet these leaders have courageously accepted their role to disrupt low performance and thus they have created environments where students learn and professors teach. These leaders are "purveyors of change." The purpose of this educational preparation supplemental text is to share stories of these exceptional leaders in the field and in the academy. The experiences shared by the various authors cover four important areas in leadership: Culture & Climate; Student Success; Resilience, Persistence, & Turnaround; and Social Justice. The authors have shared some deeply personal issues and triumphs. These are the stories that resonate more deeply with students and that with these types of stories, the theory to practice bridge is successfully crossed. While many of the chapters include narratives of resilience and triumph in the context of the P-12 education system, the overarching themes and suggestions can be transmuted to any industry"-- Provided by publisher.
Keywords: African Americans -- Education.; Minorities -- Education -- United States.; Educational leadership -- United States.; African American educators.; Community and school -- United States.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books